Influence of Thermal Treatment on The Electronic Properties of ITO Thin Films Obtained by RF Cathodic Pulverization. Study of Solar Cells Based on Silicon/(RF Sputtered) ITO Junctions - G. Campet; C. Geoffroy; S. J. Wen; J. Portier; P. Keou; J. Salardenne; Z. W. Sun (Active and Passive Electronic Components)
ITO (Indium Tin Oxide) thin films obtained by R.F cathodic sputtering have been studied. The influence of thermal treatment on the electronic properties of the films has been particularly investigated. Electrical measurements were performed between 95 and 600 K. Free carriers concentration in the film were measured by Hall effect coefficient. Optical indices were determined by computer drawing of charts allowing to simplify Manifacier method.